1992
DOI: 10.1083/jcb.118.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin heavy chain is required for pinocytosis, the presence of large vacuoles, and development in Dictyostelium.

Abstract: Abstract. To investigate the intracellular role of the clathrin heavy chain in living cells, we have used "antisense" RNA to engineer mutant Dictyostelium discoideum cells that are severely deficient in clathrin heavy chain expression. Immunoblots stained with an anti-clathrin heavy chain antiserum revealed that mutant cells contained undetectable amounts of clathrin heavy chain protein. Similarly, Northern blots showed an absence of clathrin heavy chain mRNA. Clathrin heavy chain-deficient Dictyostelium cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 45 publications
4
98
0
Order By: Relevance
“…24 and data not shown). We found that clathrin-minus cells were not as efficient at capping (Ϸ5% of mutant cells formed caps vs. Ϸ50% of wild-type cells), possibly due to swelling of the mutants in the hypotonic buffer used in the capping assay (19). Nonetheless, the ability of clathrin-minus cells to form Con A caps contrasted markedly with the complete failure of myosin II-null mutants to form caps.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…24 and data not shown). We found that clathrin-minus cells were not as efficient at capping (Ϸ5% of mutant cells formed caps vs. Ϸ50% of wild-type cells), possibly due to swelling of the mutants in the hypotonic buffer used in the capping assay (19). Nonetheless, the ability of clathrin-minus cells to form Con A caps contrasted markedly with the complete failure of myosin II-null mutants to form caps.…”
Section: Resultsmentioning
confidence: 51%
“…We recently engineered Dictyostelium cell lines that are devoid of clathrin heavy chain and identified defects in specific membrane traffic events such as endocytosis and regulated secretion (15,19). Clathrin-minus cells also were blocked in development (17).…”
Section: Resultsmentioning
confidence: 99%
“…Clathrin-deficient Dictyostelium cells show dramatic morphological and functional defects of the CV (O'Halloran and Anderson, 1992;Wang et al, 2003). Deletion of the apm1 gene encoding the medium subunit of the clathrin adaptorprotein AP-1 also results in the absence of a characteristic CV (Lefkir et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Essentially all of the internalized fluid phase is exocytosed from cells from postlysosomes, beginning approximately 45 min after internalization; no early endosomal recycling compartment has been identified (Aubry et al, 1993;Padh et al, 1993). Endocytosis is regulated by a number of proteins in Dictyostelium including the clathrin heavy chain (O'Halloran and Anderson, 1992;Ruscetti et al, 1994), the actin cytoskeleton (Temesvari and Cardelli, unpublished results), the vacuolar H+-ATPase (Temesvari et al, 1996a), select myosin I molecules (Novak et al, 1995;Jung et al, 1996;Temesvari et al, 1996b), and phosphatidylinositol 3-kinases (Buczynski et al, 1997). It is currently not known how much the clathrin-dependent and -independent pathways individually contribute to pinocytosis.…”
Section: Introductionmentioning
confidence: 99%